Memahami Tren “Atribut Produk”: Tinjauan Perilaku Konsumen dalam Memilih Produk Minuman dan Implikasinya Terhadap Industri - Efawati, Yen; Nanang Juhandi Hermawan (Asosiasi Ahli Administrasi Indonesia, 2020)
This study aims to analyze the product attributes that influence consumer purchasing decisions. Study phenomena are limited to attributes of healthy drink products. The approach uses the quantitative in a total of 84 respondents from economics college in Bandung city who consume health softdrink products. Sampling using with simple random sampling method and regression analysis approach was applied to test the research model. The results of the analysis show that brand and quality have a significant influence on consumers’ purchasing decisions, while labels and packaging do not have a significant effect. However, simultaneously, brands, labels, quality, and packaging influences on purchasing decisions that are equal to 84.9%. The rest is influenced by other variables outside the product attributes variable. This research highlights the product attributes which are the most important elements in the marketing process because they can add value to consumers. This shows that product attributes need to be paid attention to and improved to be competitive with similar products.